Physical Properties of an Alfisol Under Biofuel Crops in Ohio - Bonin, Catherine; Lal, Rattan (Journal of Technology Innovations in Renewable Energy, 2012)
There is an increasing need to develop renewable energy sources from biofuel crops to replace fossil fuels. Biofuel crops may also enhance ecosystem functions such as soil quality, water availability, and nutrient reserves. Therefore, the effects of four biofuel crops (corn (Zea mays), switchgrass (Panicum virgatum), indiangrass (Sorghastrum nutans) and willow (Salix spp.) were evaluated on soil quality at three sites in Ohio to assess the effects of crop species on soil bulk density (ρb), soil moisture characteristics (SMC), water stable aggregate distribution (WSA), and aggregate tensile strength (TS) to 40 cm depth. Overall, results were site-specific, with most differences occurring for the clayey soil at the Northwest site. At the Jackson site, soil in the 0-10 cm layer under switchgrass had a higher moisture content (θ) between 0 and 100 kPa than that under indiangrass. At the Western site, θ under corn at 1500 kPa was higher at 30-40 cm depth. At the Northwest site, soils under corn in the 0-10 cm depth tended to have the lowest θ at 0 and 3 kPa, while soils under switchgrass and willow had 50% more large macroaggregates and fewer small microaggregates than that under corn. Soil TS in the 0-10 cm depth under corn was nearly 160% more than that under other perennial crops. These results suggest that management of perennial biofuel crops can improve soil physical quality. Changes over seven years occur first in the surface soil layers, but further differences may evolve in subsoil layers with increase in time.